PENGARUH PAJAK, TUNNELING INCENTIVE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KEPUTUSAN TRANSFER PRICING (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2021) - Admaja Elwiska; Zirman Zirman; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of tax, tunneling incentive, profitability andfirm size on transfer pricing decisions. This population of this study is MiningCompany listed on the Indonesia Stock Exchange (IDX) in the 2016-2021 period.The research sample was selected using the purposive sampling method. The sampleselected in this study was 8 companies and selected based on predetermined criteria. Thedata analysis method used is multiple linear regression. The result of the study show thattax and tunneling incentive has positive effect on transfer pricing decisions partially.Meanwhile, profitability and firm size have no effect on transfer pricing decisions. Key words:Tax, Tunneling Incentive, Profitability, Firm Size, TransferPricing Decisions